Biothreat Reduction and Economic Development: The Case of Animal Husbandry in Central Asia - Walker, Robert; Blackburn, Jason (Frontiers in Public Health, 2015)
Improving human welfare is a global concern, but not always easy to achieve. In this regard, challenges have been faced by the states of the Former Soviet Union (FSU), where socialist institutions have disappeared, and the transition to a market economy has been slow. Economic adjustments have been difficult in the new nations of central Asia, including Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan. Here, a severe climate limits agriculture, and industrialization has been inhibited by a lack of infrastructure, human capital, and financial resources. These conditions are aggravated by the fact that the central Asia is mostly landlocked, far from market centers. Despite these barriers, development potential exists, and the goal of the paper is to consider central Asia’s pastoral economy, with a focus on Kazakhstan, which stands poised to become a regional growth pole. The article pursues its goal as follows. It first addresses the biothreat situation to central Asian livestock herds, a significant impediment to realizing the market potential of the region’s animal products. It next provides an outline of interventions that can reduce risk levels for key biothreats impacting central Asia, namely foot and mouth disease (FMD) and Brucellosis. Included is a success story involving FMD eradication in Brazil, which enabled an export boom in beef. After this comes a description of the epidemiological situation in Kazakhstan; here, the article considers how wildlife might act as a disease reservoir, which presents a conservation issue for the Kazakhstani case. This is followed by a discussion of the role of science in threat reduction, particularly with respect to the potential offered by geospatial technologies. The article concludes with an assessment of the research that would be necessary to identify pathways to developing the economic potential of central Asia, as changes in policy are implemented and livestock health improves.